Integrating Long- and Short-Term Contracting via Business-to-Business Exchanges for Capital-Intensive Industries - Kleindorfer, Paul R.; Wu, D. J. (Management Science, 2003)
This paper surveys the underlying theory and practice in the use of options in support of emerging business-to-business (B2B) markets. Such options, on both capacity and output, play an important role in integrating long- and short-term contracting between multiple buyers and sellers in such markets. This trend is especially important in capital-intensive industries, where improvements in fine tuning the coordination of supply and demand carry large economic benefits. Typically, such options are benchmarked (or defined) on the basis of spot market information conveyed through near real-time B2B transactions. This paper notes broad set of goods and services currently being traded in both B2B short-run markets and long-term contract markets, and reviews economic and managerial frameworks that have been proposed to explain the structure of contracting in these markets. We provide a general framework based on transactions cost economics, and we use this framework to provide review and synthesis of existing literature to explain various types of contracting linked to B2B exchanges in capital-intensive industries. The paper concludes with a discussion of implementation challenges and open research questions.